Survey Paper on User-Centric Service Composition - Henry Rossi Andrian; Wardani Muhamad (IJAIT (International Journal of Applied Information Technology), 2021)
Service composition combines several services to complete more complex tasks and get increased service value. The service user determines the task be completed. Several standards have been presented to support the composition of services, including BPEL and WSCDL. However, existing standards can only be used or operated by IT professionals who understand software design and development well. The number of end-users who do not have specific skills is far greater than that of IT professionals. Therefore, to improve service composition capabilities, end-users must be given the opportunity to interact directly with the service composition system to obtain the new services they need. To create a user-centered service composition, some general needs must be met, namely: making it easier for users to obtain appropriate services, guaranteeing the fulfillment of Quality of Service (QoS), and visualizing composite services that are generated instantly. The resulting services meet external requirements submitted directly by users and pay attention to user preferences as internal (implicit) requirements. This paper presents various studies that have been produced to support the composition of user-centered services and problems that are still open as to research challenges in the future. This study's results are exspected to help service composition platform developers understand the various approaches to developing user-centered service composition.